Ability of optical coherence tomography to detect caries beneath commonly used dental sealants - Holtzman, Jennifer S.; Osann, Kathryn; Pharar, Jessica; Lee, Kenneth; Ahn, Yeh-chan; Tucker, Travis; Sabet, Sharareh; Chen, Zhongping; Gukasyan, Ripsik; Wilder-Smith, Petra (Lasers in surgery and medicine, 2010)
Background and Objective The onset and progression of early tooth decay is often preventable with dental sealants. However, occasionally decay progresses underneath the sealant. Current technology does not permit monitoring of potential lesion progression or arrest. Dental sealants themselves mask the visual cues that identify early tooth decay, and radiographs are not sufficiently sensitive. Therefore, clinicians can be reluctant to use dental sealant. The objective of this ex vivo study was to evaluate the ability of dentists to detect decay beneath commonly used dental sealants using optical coherence tomography (OCT) imaging. Study Designs/Materials/Methods Forty extracted teeth were divided into equal groups of carious and non‐carious teeth, as determined by visual inspection. After radiographs and OCT imaging, teeth were randomly assigned for sealant placement with one of four commonly purchased dental sealants: Clinpro™, Fuji Triage™, Embrace Wet Bond™, and Delton™. Following sealant placement, teeth were radiographed, imaged with OCT, sectioned, examined histologically, and scored as healthy/not healthy. OCT and radiographic images were scored separately. The gold standard was histopathological diagnosis from the serial sections. Cohen's kappa, sensitivity, negative predictive value, and positive predictive value were computed for all measures. Results After 90 minutes training, pre‐standardized dentists were able to detect tooth decay more accurately using OCT than with visual or radiographic examination. Detection using OCT was somewhat better prior to sealant placement than afterwards. This effect varied in size depending on the type of sealant used. Radiographic diagnosis was also less accurate after sealant placement. Of the four dental sealants, Delton provided excellent positive predictive value and the best post‐sealant negative predictive values. Conclusion In this ex vivo study, dentists were able to detect tooth decay beneath four commonly used dental sealants based on OCT images. Clinical investigations are now underway to determine the usefulness of this approach in vivo. Lasers Surg. Med. 42:752–759, 2010 © 2010 Wiley‐Liss, Inc.